1989
DOI: 10.1192/s0007125000297535
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Tolerability of Moclobemide Compared with Imipramine in Depressive Disorder (DSM-III): An Austrian Double-blind, Multicentre Study∗

Abstract: The antidepressant efficacy, tolerability, and safety of moclobemide, a reversible, monoamine oxidase-A inhibitor, were compared with those of imipramine in parallel groups of patients with a major depressive episode, in a 4-week, multicentre (17 centres), randomised study. A total of 381 patients were randomly allocated to either treatment; they were not required to avoid tyramine-rich foods. Drop-out rates were comparable in both groups at about 17%. Judged primarily on the HRSD, no significant differences i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
42
0
1

Year Published

1996
1996
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(49 citation statements)
references
References 6 publications
6
42
0
1
Order By: Relevance
“…Unfortunately, moclobemide although successfully used in Europe was never registered for the US market. Data from clinical studies (Stabl, Biziére, Schmid-Burgk, & Amrein, 1989;Baumhackl et al, 1989;Versiani et al, 1989;Kok & Tsoi, 1995;Rimón et al, 1993;Silverstone et al, 1994) suggested that moclobemide treatment was superior to placebo and comparable, as judged by an improvement of the HAM-D rating score, to imipramine, a tricyclic antidepressant, in studies treating patients suffering from major depressive disorders. The doses applied ranged from 75 mg/d to 600 mg/d and the response rates reported from 50% to 70%.…”
Section: Depressionmentioning
confidence: 99%
“…Unfortunately, moclobemide although successfully used in Europe was never registered for the US market. Data from clinical studies (Stabl, Biziére, Schmid-Burgk, & Amrein, 1989;Baumhackl et al, 1989;Versiani et al, 1989;Kok & Tsoi, 1995;Rimón et al, 1993;Silverstone et al, 1994) suggested that moclobemide treatment was superior to placebo and comparable, as judged by an improvement of the HAM-D rating score, to imipramine, a tricyclic antidepressant, in studies treating patients suffering from major depressive disorders. The doses applied ranged from 75 mg/d to 600 mg/d and the response rates reported from 50% to 70%.…”
Section: Depressionmentioning
confidence: 99%
“…Vallejo et al (1987) 139 Imipramine, phenelzine Phenelzine Ͼ imipramine Baumhackl et al (1989) 140,b Moclobemide, imipramine Moclobemide = imipramine Ravindran et al (1994) 158 Fluoxetine 65% response Marin et al (1994) 135,a Desipramine 70% response 159,a Desipramine 61% response Kocsis et al (1996) 160,a Desipramine 71% response Dunner et al (1996) 23 Fluoxetine Fluoxetine = CBT Dunner et al (1997) 150 Venlafaxine Ͼ70% response Keller et al (1998) 132,c Sertraline, imipramine Sertraline = imipramine Santagostino et al (1998) 161 Alprazolam 73% response Smeraldi (1998) 162 Amisulpride, fluoxetine Amisulpride = fluoxetine Ravindran et al (1998) 151 Venlafaxine Kocsis et al 166 indicated that the higher relapse rate in those dysthymic patients who were randomized to placebo exceeded that of patients who continued on the maintenance desipramine treatment. Paralleling these findings, symptom improvement was sustained, and the rate of relapse reduced, among dysthymic patients who were maintained on either trazodone or fluoxetine over a 40-week interval compared to those who discontinued medication.…”
Section: Non-placebo-controlledmentioning
confidence: 99%
“…Moreover, it has been suggested that optimal drug effects would be obtained when administered primarily to patients with subaffective, rather than character spectrum disorder. 4 In fact, studies which employed rigorous diagnostic criteria, established the efficacy of tricyclic agents, such as imipramine and desipramine, [131][132][133][134][135][136][137] MAOIs, 136,138,139 the reversible monoamine oxidase inhibitor, moclobemide, 114,137,[140][141][142][143] SSRIs, such as fluoxetine and sertraline, 22,23,111,132,134,[144][145][146] as well as other agents, such Molecular Psychiatry as the 5HT 2 antagonist, ritanserin, 147,148 the selective norepinephrine reuptake inhibitor, reboxetine, 149 and the serotonin/norepinephrine reuptake inhibitor (SNRI), venlafaxine 150,151 (Table 1). The use of well tolerated compounds, including moclobemide and sertraline, may be effective in the long-term management of dysthymia.…”
Section: Pharmacological Contributions To the Analysis Of Dysthymiamentioning
confidence: 99%
“…This ®nding is in keeping with the ®ndings of an Austrian multicentre trial of moclobemide vs. imipramine which included 33 bipolar patients (15), but contrasts with a metaanalysis of clinical trials of moclobemide in depression in which MCB appeared to be superior to a range of comparators, including IMI, in the minority of patients who were deemed to have bipolar depression (7). In our study, all the patients were bipolar, and met the diagnostic criteria for bipolar disorder laid down in DSM-III-R.…”
Section: Discussionmentioning
confidence: 84%